IMPROVEMENT OF ELEMENTS OF TECHNOLOGY OF CULTIVATION OF HEIFERS IN THE MILK PERIOD - Antonenko, S. F.; Piskun, V. I.; Rudenko, E. V.; Chyhrynov, E. I.; Zolotarev, A. P.; Osypenko, Т. L.; Sikun, M. V. (Scientific Progress & Innovations, 2022)
Important factors that affect the formation of future productivity of cows are the method jf keeping calves colostrum and dairy periods of consistency of composition and size of the number of technological groups of heifers in different periods of ontogenesis. A significant problem is the lack of clear positions on the size of technological groups in the of calves from individual to groups housing, allowable indicators of variability of live weight, age of heifers in the formation of the technological groups, the size of the feeding front in calves. The article presents the results of research to improve the cuitivation of heifers of the Ukrainian black – and – white breed in the conditions of SE Kutuzivka kharkiv region. The scientific and economic experiment was focused on substantiating the effectiveness of the influence of different numbers of heifers in the technological groups on their growth and development in milk period of ontogenesis. It was found that the actual difference in feed consumption in each series of experiments between animals in each group of 5 – 10 – 15 – 20 heads and a den area of 1,8 m2 – 2,2 m2 on deep straw litter was not detected. And when comparing technological groups: 5–20, 10–20, 15–20 heads, a difference was found. It is experimentally proved that the bse of growing heifers for 10 days of age up to 6 months loose on deep straw litter in groups sections of 5–10 and 15 heads compared with 20 goals, increased the increase in live weight gain on average during the experiment by 13,7–19,0 % (P<0,05). It is established that the technology of cultivation in autumn – winter period in the premises of light type contributes to the increase of the average daily increase from 16,7 to 23,3 % (P<0,05). Under these conditions of growing heifers in technological groups of 5, 10 and 15 heads in comparison with analogues – 20 heads there is a reduction in feed costs per 1. According to the results of multicriteria analysis, it was found that the content of heifers in the technological group of 15 heads and an area of 2.2 m2 per head was the best, the target function for which according to the considered criteria was lower and was 0.0877. Other options were 1.0160–3.3854 times worse.